Determinants of Financial Performance of Microfinance Institutions: A Comparative Case Study on Selected Microfinance Institutions in Uganda - Mayende, Constant Othieno (Digital Repository of Theses - SSBM Geneva, 2025)
This research investigates the determinants of financial performance among microfinance institutions (MFIs) in Uganda, adopting a comparative case study design and a mixed-methods approach. Given the critical role MFIs play in advancing financial inclusion, supporting small enterprises, and alleviating poverty among underserved populations (Armendáriz and Morduch, 2010; Ledgerwood, 1999), understanding the drivers of their financial sustainability is both timely and essential. The research improves MFIs’ role in socio-economic development by identifying and analyzing internal and external factors that impact financial performance. Specifically, it investigates governance quality, management skills, operational efficiency, risk management practices, technological adaptation, regulatory frameworks and macroeconomic conditions (Cull et al., 2009; Mersland and Strøm, 2009). Quantitative and qualitative data was collected from selected MFIs in Kampala Central Business District. Regression analysis was used to examine relationships between institutional features and financial metrics such as Return on Assets (ROA), Return on Equity (ROE), and Operational Self Sufficiency (OSS) (Rosenberg, 2009), while in-depth interviews with board members, executives and managers provided additional perspective-based insights (Yin 2018). The findings reveal that financial performance is multifaceted, shaped by institutional capacity and the external environment. Governance structures emerged as significant predictors, with effective oversight and accountability strongly linked to MFI profitability. Operational efficiency had a weaker positive effect, suggesting efficiency gains must be complemented by sound governance. Macroeconomic stability, particularly controlled inflation and exchange rate stability was one of the most robust determinants underpinning institutional resilience. Conversely, management quality showed no significant effect, highlighting persistent gaps in leadership capacity and autonomy. Technological adaptation demonstrated weak or negative effects due to high costs, limited staff expertise and poor alignment of digital solutions with institutional needs. Risk management practices were correlated with performance but did not emerge as independent predictors, reflecting their role as buffers rather than direct enhancers. In conclusion, the study affirms that financial performance of Ugandan MFIs depends on a balanced mix of strong governance, operational efficiency, supportive regulation and macroeconomic stability, while addressing weaknesses in management, risk management and technological integration. These findings contribute to the literature on microfinance sustainability and provide actionable insights for policymakers, regulators and practitioners seeking to strengthen resilience and long-term impact in low-income economies.